Segmented electroforming method for metal microstructure core
Through the segmented electroforming method, the metal microstructure core is divided into multiple electroforming layers, and electroforming is carried out using a combination of different current density and pulse current, which solves the problems of low replication accuracy, warping and deformation and production efficiency in the prior art, and achieves efficient and precise core manufacturing.
Patent Information
- Application Number
- CN202411761174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
When the existing electroforming method manufactures metal microstructured cores, there are problems such as low replication accuracy, easy warping of the core, easy occurrence of edge tumors, and low production efficiency.
The metal microstructure core is divided into microstructure layer, transition layer and base layer by using segmented electroforming method, and the thickness and power supply parameters of each electroforming layer are determined separately, and electroformed is performed by combining different current densities and pulse currents.
It improves the replication quality of the die core, reduces warping and deformation and thickness unevenness, shortens the processing cycle, improves processing efficiency, and extends the service life of the die core.
Smart Images

Figure CN119221046B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of micro-manufacturing technology, and in particular to a segmented electroforming method for a metal microstructure mold core. Background Art
[0002] In polymer micron-scale manufacturing, microinjection molding is often used for mass production of functional polymer microdevices, such as microfluidic devices, micro-optics and anti-stick surfaces, due to its high throughput, low manufacturing cost and high replication accuracy. In the injection molding of polymer microdevices, precision metal microstructure core manufacturing technology is one of the key technologies to achieve mass production of polymer microdevices. In the LIGA technology from Germany, the use of micro-electroforming with high manufacturing accuracy (atomic level deposition) and low cost to prepare metal microstructure cores is one of the main schools of core micromanufacturing in the world.
[0003] Backplane electroforming is an electroforming method that deposits microstructures and core substrates at the same time, and has the following characteristics: long molding time, high bonding strength between microstructure and core substrate, long core life, and is suitable for metal microstructure core manufacturing. However, this method has problems such as low core microstructure replication accuracy, easy warping and deformation of the core as a whole, easy edge tumors on the core surface during the electroforming process, and low production efficiency. Therefore, how to improve the electroforming efficiency of the core under the premise of meeting the special requirements of polymer microdevices in terms of microchannel quality, chip flatness, and thickness uniformity is the key to realizing mass production and industrial application of polymer microdevices. At present, the patent technology in this field mainly focuses on the processing method of electroforming master molds, the mass production method of polymer microdevices, and the improvement of the performance of electroforming cores. There is no patent technology that improves the processing efficiency while ensuring the performance of the electroforming core. Summary of the invention
[0004] The embodiment of the present application provides a segmented electroplating method for a metal microstructure mold core, which aims to improve the quality of microstructure replication, reduce the warping deformation and thickness unevenness of the mold core, while effectively exerting the advantages of the segmented electroplating method, shortening the processing cycle, and improving processing efficiency.
[0005] To achieve the above-mentioned purpose, the present application provides a segmented electroforming method for a metal microstructure mold core, which divides the metal microstructure mold core into a microstructure layer, a transition layer and a base layer, and determines the thickness of each electroforming layer respectively. The segmented electroforming method comprises the following steps:
[0006] S1. Photolithography and pre-processing of electroplating master mold;
[0007] S2. Arrange the electroforming device and set the power supply parameters: install the electroforming mother mold on a cathode fixture containing a side sealing liquid tank, the side sealing liquid tank is used to suppress the edge effect of the casting layer cathode, the cathode fixture is installed on a rotating mechanism, an insulating shielding baffle with a through hole is arranged between the electroforming mother mold and the anode, two flushing ports are symmetrically arranged in the electroforming tank, the two flushing ports are aligned with the through hole of the insulating shielding baffle and the electroforming mother mold, and the electroforming liquid impacts the electroforming mother mold, the electroforming liquid is mainly nickel sulfamate; according to the thickness of each electroforming layer, the power supply parameters of each electroforming layer are correspondingly set on the same pulse power supply;
[0008] S3. Using a current density of 0.5-1A / dm on the electroforming master mold 2 The microstructure layer is formed by direct current or reverse pulse current electroforming:
[0009] For the microstructure layer with an aspect ratio less than or equal to 1, a current density of 0.5-1A / dm 2 The electroforming master mold is rotated while applying a direct current to perform electroforming;
[0010] For the microstructure layer with a depth-to-width ratio greater than 1, a reverse pulse current is used while rotating the electroforming master mold for electroforming, wherein one pulse cycle of the reverse pulse current includes a positive current and a negative current;
[0011] S4. Forming the transition layer on the microstructure layer by electroforming with a positive pulse current: switching the current for electroforming the microstructure layer to a positive pulse current without interruption, and forming the transition layer on the microstructure layer by electroforming with a positive pulse current;
[0012] S5. Using a current density of 3-5A / dm on the transition layer 2 The base layer is formed by electroforming with a direct current: the positive pulse current for electroforming the transition layer is switched continuously to a current density of 3-5A / dm 2 A direct current is applied to electroform the base layer on the transition layer;
[0013] S6. Post-processing of the metal microstructure core after electroforming.
[0014] Optionally, the thickness of each electroformed layer is determined as follows:
[0015] The thickness of the microstructure layer is 0.5 times the width of the characteristic microstructure in the metal microstructure mold core;
[0016] The thickness of the transition layer is 220µm: the thickness of the transition layer is determined based on simulation and experimental results, the thermal stress generated by the temperature load is used to simulate the stress caused by the expansion or contraction of the transition layer, the relationship between the tensile stress and the temperature load measured in the experiment is established based on the following two formulas, and the relationship between the thickness change of the transition layer and the warpage deformation is analyzed; in the experiment, a transition layer of 60-260µm is electroformed on a single mirror-polished silicon substrate, and the maximum warpage deformation is tested using an ultra-depth of field microscope. When the experimental and simulation results both show that when the thickness of the transition layer is 220µm, the maximum warpage deformation no longer changes;
[0017] ;
[0018] ;
[0019] In the formula represents the temperature load change, represents Poisson's ratio, represents the elastic modulus, represents the experimentally measured tensile stress, is the coefficient of thermal expansion, represents the process temperature, Indicates the equivalent reference temperature;
[0020] The thickness of the base layer is the total thickness of the metal microstructure core minus the thickness of the microstructure layer and the transition layer.
[0021] Optionally, in step S3, for the microstructure layer with an aspect ratio less than or equal to 1 and for the microstructure layer with an aspect ratio greater than 1, the rotation speed of the electroforming master mold is 120 r / min;
[0022] For the microstructure layer with an aspect ratio greater than 1, the frequency of the reverse pulse current is 0.1-10 Hz, and the forward current density is 1 A / dm 2 , the positive-negative pulse ratio is 1:6, and the negative pulse duty cycle is 0.1-0.2.
[0023] Optionally, in step S4, the frequency of the forward pulse current is 800 Hz, and the average current density is 1 A / dm 2 , the duty cycle is 0.5.
[0024] Optionally, in step S1, photolithography and pre-processing of the electroforming master mold includes the following steps:
[0025] S11. Design a polymer micro-device mask, introduce an edge micro-groove structure, select a negative SU-8 photoresist as the lithography object, and complete the preparation of the electroplating master mold through the processes of coating, pre-baking, exposure, post-baking, development and hardening;
[0026] S12. A layer of titanium or chromium is plated on the electroforming master mold as a bonding layer;
[0027] S13. A layer of metal platinum is plated on the bonding layer as a conductive layer.
[0028] Optionally, in step S12, at a vacuum degree of 5×10 -2 MPa and a sputtering current of 100-120 mA, and the sputtering time is 100-200 s;
[0029] In step S13, the vacuum degree is 5×10 -2 The conductive layer is plated under the conditions of a pressure of 100 MPa and a sputtering current of 35 mA, and the sputtering time is 100-300 s.
[0030] Optionally, in step S6, post-processing the electroformed metal microstructure mold core comprises the following steps:
[0031] S61. Prepare a sodium hydroxide solution, place the metal microstructure core into the solution, and dissolve silicon by ultrasonic stirring and heating the sodium hydroxide solution;
[0032] S62. The metal microstructure mold core is then placed in an acetone solution and the SU-8 photoresist on the surface is removed by ultrasonic stirring;
[0033] S63. Finally, the metal microstructure mold core is placed in an ethanol solution, and the residual SU-8 photoresist in the microstructure layer is removed by ultrasonic treatment.
[0034] Optionally, in step S61, a 30 wt% sodium hydroxide solution is prepared, the heating temperature is 80° C., the ultrasonic power is 100 W, and the stirring time is 20 min;
[0035] In step S62, the temperature of ultrasonic treatment is room temperature;
[0036] In step S63, ultrasonic treatment is performed at room temperature for 30 minutes.
[0037] The segmented electroforming method of the metal microstructure mold core provided in the present application has at least the following beneficial effects:
[0038] 1. Improved processing efficiency of metal microstructure mold core: The conventional one-stage electroforming method will select a smaller current density, and the electrodeposition rate is low, resulting in a too long electroforming cycle of the mold core. The segmented electroforming method of the present application deposits the microstructure layer and the transition layer at a low speed, deposits the base layer at a high speed, clarifies the thickness of each layer, and enables the current switching without intervals at the segment, which can significantly improve the electroforming efficiency on the basis of ensuring the performance of the metal microstructure mold core;
[0039] 2. Ensure the complete deposition of the microstructure layer in the metal microstructure core, the high flatness of the transition layer and the high thickness uniformity of the substrate layer, and realize the electroforming of the precision metal microstructure core; use the principle of deposition and dissolution of the reverse pulse current to effectively improve the nickel filling rate in the microstructure; use the positive pulse and edge microgroove to assist in increasing the dislocation density of the nickel core, reducing the internal stress and increasing the mechanical contraction force between the metal microstructure core and the substrate, and minimize the warping deformation caused by the high stress during the electroforming process; use the insulating shielding baffle and the side sealing liquid groove to effectively avoid the electric field line aggregation at the edge of the metal microstructure core;
[0040] 3. Ensure that there is no obvious interface at the electroforming segment of the metal microstructure core to improve the service life of the segmented metal microstructure core: The uninterrupted current switching between layers during the electroforming process of the metal microstructure core can make the Ni grains grow continuously, avoiding the lattice mismatch of Ni regrowth caused by long-term intervals at the segment and oxidation at the interface, resulting in poor interlayer bonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] in:
[0043] Figure 1 It is a structural schematic diagram of a metal microstructure mold core formed by electroforming using a segmented electroforming method according to an embodiment of the present application;
[0044] Figure 2 It is a schematic diagram of a process of a segmented electroforming method according to an embodiment of the present application;
[0045] Figure 3 It is a schematic diagram of the process flow of the pre-treatment stage in step S1 of the segmented electroforming method shown in one embodiment of the present application;
[0046] Figure 4 1 is a schematic diagram of power supply parameters set on a pulse power supply in step S2 of a segmented electroforming method according to an embodiment of the present application, wherein: Figure 4 (1) The aspect ratio of the corresponding microstructure layer is less than or equal to 1; Figure 4 (2) The aspect ratio of the corresponding microstructure layer is greater than 1;
[0047] Figure 5 is a schematic diagram of a reverse pulse current deposited microstructure layer in step S3 of a segmented electroforming method according to an embodiment of the present application, wherein: Figure 5 (1) is a schematic diagram of using reverse pulse current; Figure 5 (2) Schematic diagram of achieving complete filling of high aspect ratio microstructures by reverse pulse current;
[0048] Figure 6 is a schematic diagram of a transition layer deposited by a forward pulse current in step S4 of a segmented electroforming method according to an embodiment of the present application, wherein: Figure 6 (1) is the change of current density over time at low frequency; Figure 6 (2) is the graph of the change of current density over time at high frequency; Figure 6 (3) represents the pulse current on the cathode surface Ni 2+ Influence diagram of concentration distribution;
[0049] Figure 7 1 is a simulation and implementation data diagram of the process of determining the thickness of the transition layer in the segmented electroforming method shown in an embodiment of the present application, wherein: Figure 7 (1) and 7 (2) are schematic diagrams of the warping deformation of transition layers with thicknesses of 60 µm and 220 µm, respectively, in thermal stress simulation; Figure 7 (3) and 7 (4) are schematic diagrams of the warping deformation of transition layers with thicknesses of 60µm and 220µm respectively observed using an ultra-depth of field three-dimensional microscope in the experiment;
[0050] Figure 8 It is a schematic structural diagram of an electroforming device used in a segmented electroforming method shown in one embodiment of the present application.
[0051] Description of main component symbols:
[0052] 1. Electroforming tank; 11. Flushing port; 2. Anode; 3. Electroforming mother mold; 4. Cathode fixture; 41. Side sealing tank; 5. Rotating mechanism; 6. Insulating shielding baffle; 61. Through hole; h. Thickness of microstructure layer; D. Through hole diameter of insulating shielding baffle; H. Distance between insulating shielding baffle and electroforming mother mold; B. Height of side sealing tank. DETAILED DESCRIPTION
[0053] In order to facilitate the understanding of the present application, the present application will be described more comprehensively with reference to the relevant drawings below. The preferred embodiments of the present application are provided in the drawings. However, the present application can be implemented in many other different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0054] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0056] The present application provides a segmented electroforming method for a metal microstructure mold core, establishes the relationship between power supply parameters and microstructure forming, internal stress and electric field shielding and thickness distribution uniformity, and systematically divides the electroforming process into three sections, corresponding to the microstructure layer, transition layer and base layer of the metal microstructure mold core, respectively, clarifies the thickness of each layer and ensures seamless current switching at the segment.
[0057] like Figure 1 As shown, the metal microstructure core (with a total thickness of 1 mm) is divided into a microstructure layer, a transition layer and a base layer. The thickness of each layer is determined as follows:
[0058] The thickness of the microstructure layer (i.e., h in the figure) is determined according to the characteristic microstructure width in the metal microstructure core. The thickness of the microstructure layer is 0.5 times the characteristic microstructure width to ensure complete deposition of the microstructure while improving the electroforming efficiency. For example, if the characteristic microstructure width is 60µm, the thickness h of the microstructure layer is 30µm.
[0059] The thickness of the transition layer is 220µm. A transition layer with a thickness of too small cannot effectively resist the warping deformation of the substrate layer in the third stage of high current electroforming, while a transition layer with a thickness of too large seriously affects the electroforming efficiency. The optimal transition layer thickness is determined based on simulation and experimental results. The thermal stress generated by the temperature load is used to simulate the stress caused by the expansion or contraction of the transition layer. The relationship between the tensile stress and the temperature load measured in the experiment is established based on the following two formulas, and the relationship between the change in the thickness of the transition layer and the warping deformation is analyzed. In the experiment, a transition layer with a thickness of 60-260µm was electroformed on a single mirror-polished silicon substrate, and the maximum warping deformation was tested using an ultra-depth of field microscope. Both the experimental and simulation results show that when the thickness of the transition layer reaches 220µm, the maximum warping deformation no longer changes significantly, indicating that the transition layer with a thickness of 220µm has sufficient rigidity to effectively resist the warping deformation caused by the internal stress of the casting layer;
[0060] ;
[0061] ;
[0062] In the formula represents the temperature load change, represents Poisson's ratio, represents the elastic modulus, represents the experimentally measured tensile stress, is the coefficient of thermal expansion, represents the process temperature, Indicates the equivalent reference temperature.
[0063] Specifically, when the thickness of the transition layer is determined, the thermal expansion subnode in the Comsol solid mechanics module is used to perform thermal stress simulation. A fixed displacement constraint is applied to the square with a side length of 1 mm at the center of the bottom of the casting layer. The warping deformation of the transition layer with a thickness of 60 µm and 220 µm is shown as follows: Figure 7 (1) and Figure 7 (2) shows that the maximum warpage deformation is 710µm and 149µm respectively. The warpage deformation of the transition layer with thickness of 60µm and 220µm respectively under the same conditions was characterized by using ultra-depth 3D microscopy. Figure 7 (3) and Figure 7 As shown in (4), the maximum warpage deformation is 557µm and 221µm respectively. After further increasing the thickness of the transition layer, both simulation and experimental results show that the warpage deformation no longer changes significantly, indicating that the transition layer with a thickness of 220µm has sufficient rigidity to effectively resist the warpage deformation caused by the internal stress of the casting layer. Considering the need to reduce the warpage deformation while improving the electroforming efficiency, the thickness of the transition layer is selected to be 220µm.
[0064] The thickness of the base layer is the total thickness of the metal microstructure core minus the thickness of the transition layer and the base layer, which is 0.75 mm.
[0065] The traditional electroforming process of metal microstructure cores is difficult to achieve low stress in the casting layer, high quality of the core, and high deposition efficiency at the same time. The quality of metal microstructure cores is the key to ensuring the quality and performance of polymer microdevices. It must simultaneously meet the requirements of precise electroforming of the microstructure layer, low stress in the transition layer, and efficient electroforming of the substrate layer. The determination of the thickness of the transition layer and the switching method of the current at the segment have an important influence on the performance of the segmented electroforming core.
[0066] The embodiments of the present application propose to use a segmented electroforming method to prepare a metal microstructure mold core, divide the electroforming process into three sections, define the thickness of the electroforming layer in each section, use different electroforming process parameters respectively, and switch the current uninterruptedly at the sections. While improving the replication quality of the microstructure layer and reducing the warping deformation and thickness unevenness of the mold core, the advantages of the segmented electroforming method are effectively utilized, shortening the processing cycle and improving processing efficiency.
[0067] Combination Figure 2-Figure 8 As shown, the segmented electroforming method of the metal microstructure mold core comprises the following steps:
[0068] S1. Photolithography and pre-processing of the electroplating master mold (also called "cathode").
[0069] S2. Arrange the electroforming device and set the power supply parameters: install the electroforming mother mold 3 on the cathode fixture 4 containing the side sealing liquid groove 41, the side sealing liquid groove 41 is used to suppress the edge effect of the casting layer cathode, the cathode fixture 4 is installed on the rotating mechanism 5, and an insulating shielding baffle 6 with a through hole 61 is arranged between the electroforming mother mold 3 and the anode 2. Two flushing ports 11 are arranged in the electroforming tank 1. The two flushing ports 11 are aligned with the through hole 61 of the insulating shielding baffle 6 and the electroforming mother mold 3, and the electroforming liquid impacts the electroforming mother mold 3, reducing the concentration polarization phenomenon on the cathode surface and improving the uniformity of mass transfer. The electroforming liquid in the electroforming tank 1 is mainly nickel sulfamate; it should be noted here that Figure 8 Where D is the diameter of the through hole 61 of the insulating shielding baffle 6, and D should be 2 / 3 of the diameter of the electroforming mother mold 3; H is the distance between the insulating shielding baffle 6 and the electroforming mother mold 3, which is adjusted according to the specific experimental environment, and the distance range is about 3-6 cm; B is the height of the side sealing groove 41, if the thickness of the metal microstructure mold core is 1 mm, the height of B should be 6-8 cm; the insulating shielding baffle 6 and the cathode fixture 4 containing the side sealing groove 41 should be installed before the experiment begins, and can be taken out after the electroforming experiment; according to the thickness of each electroforming layer, set the power supply parameters and electroforming time on the same dedicated pulse power supply, Figure 4 (1) and (2) are the power supply parameter settings for the electroforming process corresponding to the microstructures with small aspect ratio (less than or equal to 1) and large aspect ratio (greater than 1), respectively. The current forms of the corresponding microstructure layer are small current density DC current and reverse pulse current, and the current forms of the transition layer and substrate layer are forward pulse current and small current density DC current, respectively.
[0070] S3. Use a current density of 0.5-1A / dm on the electroforming master mold 2 Direct current or reverse pulse current electroforming to form microstructure layer:
[0071] For microstructure layers with an aspect ratio less than or equal to 1, a current density of 0.5-1A / dm 2 The DC current is less than 0.5A / dm 2 The current density will lead to a long electroforming time, while the current density greater than 1A / dm 2 The current density is likely to lead to the formation of pore defects in the microstructure. The thickness of the structural layer is 30µm and the electroforming time is 2.5-5h.
[0072] For the microstructure layer with an aspect ratio greater than 1, a reverse pulse current is used while rotating the electroforming master mold for electroforming. One pulse cycle of the reverse pulse current includes a positive current and a negative current.
[0073] S4. Use positive pulse current to electroform a transition layer with a thickness of 220µm on the microstructure layer: Switch the current of the electroformed microstructure layer to the positive pulse current without interruption, so that the Ni grains grow continuously, avoiding the lattice mismatch caused by Ni regrowth and the problem of poor interlayer bonding caused by oxidation at the interface. Use positive pulse current to electroform the microstructure layer for 18 hours to form a transition layer.
[0074] S5. Using a current density of 3-5A / dm on the transition layer 2 The base layer is formed by electroforming with a direct current: the positive pulse current of the electroforming transition layer is switched continuously to a current density of 3-5A / dm 2 The base layer is formed by electroforming on the transition layer for 12.5-21 hours. It should be noted that the current density is less than 3A / dm 2 It is not possible to achieve the effect of rapid electroforming of the substrate layer, and the current density is higher than 5A / dm 2 This can easily lead to uneven electric field distribution and reduce the thickness uniformity of the electroformed layer.
[0075] S6. Post-processing of the metal microstructure core after electroforming.
[0076] In the embodiment of the present application, the segmented electroforming method adopts low-speed electrodeposition of the microstructure layer and the transition layer, and high-speed deposition of the base layer, which can significantly improve the electroforming efficiency while ensuring the performance of the metal microstructure core; it ensures the complete deposition of the microstructure layer in the metal microstructure core, the high flatness of the transition layer and the high thickness uniformity of the base layer, and significantly improves the service life of the metal microstructure core. The principle of reverse pulse current deposition and dissolution is used to effectively improve the filling rate of nickel in the microstructure. By using the auxiliary methods of forward pulses and edge microgrooves, the dislocation density of the nickel core is increased, the internal stress is reduced, and the mechanical contraction force between the metal microstructure core and the substrate is increased, thereby minimizing the warping deformation caused by the high stress during the electroforming process. The electric field lines at the edge of the metal microstructure core are effectively avoided by using insulating shielding baffles and side sealing liquid grooves. Uninterrupted current switching between layers during the electroforming of the metal microstructure mold core can enable the continuous growth of Ni grains, avoiding the lattice mismatch of Ni regrowth caused by long-term intervals at the segmentation and oxidation at the interface leading to poor interlayer bonding, ensuring that there is no obvious interface at the electroforming segment of the metal microstructure mold core, thereby improving the service life of the segmented metal microstructure mold core.
[0077] In one embodiment, in combination Figure 3 As shown, in step S1, photolithography and pre-processing of the electroforming master mold includes the following steps:
[0078] S11. Design a polymer micro-device mask, introduce an edge micro-groove structure, select a negative SU-8 photoresist as the lithography object, and complete the preparation of the electroplating master mold through the processes of coating, pre-baking, exposure, post-baking, development and hardening;
[0079] S12. Plating a layer of titanium or chromium as a bonding layer on the electroforming master mold;
[0080] S13. A layer of metal platinum is plated on the bonding layer as a conductive layer.
[0081] Specifically, the polymer micro-device mask structure is designed according to requirements, including a liquid inlet, a liquid outlet, a reaction chamber and an edge micro-groove structure.
[0082] A polymer micro-device mask is designed, and an edge micro-groove structure is introduced to increase the mechanical contraction force between the electroforming layer and the mold core and release the stress at the micro-groove. Negative SU-8 photoresist is selected as the photolithography object, and the preparation of the electroforming master mold (cathode) is completed through the processes of photoresist coating, pre-baking, exposure, post-baking, development and hardening. The first bonding layer of metal titanium (Ti) or metal chromium (Cr) and the second conductive layer of platinum (Pt) are plated on the electroforming master mold.
[0083] In the implementation, soft lithography technology was used to prepare micro-column structures with a height of 20-120 μm. First, the silicon substrate after single-mirror polishing was cleaned with anhydrous ethanol and deionized water, and then placed on a 95°C glue baking table for 10 min. SU-8 was spin-coated at 500 rpm for 10 s and at 1600 rpm for 30 s to obtain a SU-8 layer with a thickness of about 50 μm. The electroformed master mold was baked on a 65°C hot plate for 2 min and 95°C for 9 min, and then exposed on a UV lithography machine (URE-2000 / 35L) with an exposure dose of 200 mJ / cm 2 , copy the mask structure onto the photoresist layer, bake the electroplated master mold on a drying table at 65°C and 95°C for 2min and 7min respectively, then develop it in PGMEA developer for 6min, clean it with isopropyl alcohol solution, and finally bake it on a 150°C hot plate for 5min to complete the hardening process.
[0084] In the specific implementation, the first bonding layer of titanium (Ti) or chromium (Cr) and the second conductive layer of platinum are respectively plated in a coating apparatus at a vacuum degree of 5×10 -2 MPa and a sputtering current of 100-120 mA to plate the bonding layer Ti or Cr, and the sputtering time is 100-200 s; the conductive layer platinum (Pt) is plated under a sputtering current of 35 mA, and the sputtering time is 100-300 s.
[0085] In practical applications, before electroforming, the electroforming master mold and the conductive frame are connected by conductive tape. A sealing ring is used to press the cathode fixture and the electroforming master mold tightly to prevent the electroforming liquid from leaking into the conductive frame. A silicone rubber film is placed at the bottom of the electroforming master mold to prevent the silicon wafer from being crushed. During electroforming, the cathode fixture is installed in the electroforming tank. The electroforming process current and electroforming time are set on the same dedicated pulse power supply. Finally, the current is connected. The electroforming time of each section is determined by dividing the layer thickness by the electroforming rate. The electroforming rate is 12 µm / (A / dm 2 ).
[0086] In one embodiment, in step S3, during the electroforming of the microstructure layer, for the microstructure layer with an aspect ratio less than or equal to 1 and for the microstructure layer with an aspect ratio greater than 1, the rotation speed of the electroforming master mold is 120 r / min;
[0087] For microstructure layers with an aspect ratio greater than 1, the frequency of the reverse pulse current is 0.1-10Hz and the forward current density is 1A / dm 2 , the positive-negative pulse ratio is 1:6, and the negative pulse duty cycle is 0.1-0.2. In this parameter range, Figure 5 As shown in (2), the initial outer contour of the electroformed microstructure is an inverted trapezoid, which effectively avoids the generation of pore defects.
[0088] Specifically, in the microstructure layer of the complete electroformed metal microstructure core, the electroforming process is selected according to the depth-to-width ratio of the microstructure. For structures with a depth of 60 μm and a width greater than or equal to 60 μm, a rotating cathode method is selected to accelerate the mass transfer of the electroforming liquid on the cathode surface and replenish the Ni in the microstructure in time. 2+ , at low current density 0.5-1A / dm 2 For structures with a width less than 60 μm, the microstructure layer is deposited by reverse pulse current, and the forward current density is 1 A / dm 2 When the positive-to-negative pulse ratio is 1:6, the frequency is 1 Hz, and the negative pulse duty cycle is 0.1, the complete deposition of microstructures with a high aspect ratio of 4:1 can be basically achieved.
[0089] like Figure 5 (2) As shown in the figure, under the action of forward current, Ni 2+ It is preferentially deposited in the mouth area of the microstructure, causing the shape of the microstructure to change from the initial rectangle to a trapezoid. Under the reverse pulse current, the casting layer at the mouth of the microstructure can be preferentially dissolved, which can effectively improve the thickness uniformity of the microstructure side wall and change the shape of the microstructure from a trapezoid to an inverted trapezoid, thus avoiding the generation of microstructure pore defects.
[0090] In one embodiment, in step S4, in the electroformed low stress transition layer, a forward pulse current is selected to increase the dislocation density of the Ni electroformed layer and reduce the internal stress, and the frequency of the forward pulse current is 800 Hz and the average current density is 1 A / dm 2 , the duty ratio is 0.5. At this time, the dislocation density of the transition layer prepared by electroforming is large, and the internal stress is minimized, which effectively reduces the internal stress of the electroforming layer and reduces the warping deformation of the mold core.
[0091] Combination Figure 6 As shown, Figure 6 (1) The change of current density with time at low frequency. Low frequency ensures that the double layer has enough charging time to reach the set current density. At this time, the overpotential plays a dominant role in the average stress of the electroformed layer. Figure 6 (2) is the change of current density with time under high frequency. Under this condition, the charging time coefficient (t) is large, the charging time is long, and the influence of the double-layer capacitance effect is significantly greater than the influence of the overpotential, so the stress is mainly affected by the time coefficient (t). Figure 6 (3) represents the pulse current on the cathode surface Ni 2+ The influence of concentration distribution, when the circuit is turned on, Ni 2+ Under the action of the double electric layer, it reaches the cathode surface, obtains electrons and undergoes a reduction reaction, so the Ni near the cathode 2+ The concentration is significantly reduced, and when the circuit is cut off, the Ni on the cathode surface 2+ Stop consumption and the Ni in the electroforming solution 2+ Due to diffusion, Ni 2+ Concentration, which is beneficial to increase the nucleation rate of nickel atoms in the deposited layer, reduce the grain size and increase the dislocation density, and reduce the internal stress of the electroformed mold core. In the electroformed substrate layer with high thickness uniformity, a larger DC current density of 3-5A / dm is selected. 2 Electrodeposited base layer, combined Figure 8 As shown, by flushing the electroforming master mold 3 with liquid, the ion mass transfer on the cathode surface is accelerated, the bubbles on the surface are flushed in time, and the surface quality of the electroforming layer is effectively improved; an insulating shielding baffle 6 is introduced between the anode and cathode, and the insulating shielding baffle 6 should be close to the wall of the electroforming tank 1 to prevent the electroforming liquid from flowing from both ends of the insulating shielding baffle 6 to the surface of the electroforming master mold 3. An insulating foam tape can be introduced between the insulating shielding baffle 6 and the electroforming tank 1 as a buffer layer to effectively improve the uniformity of the electric field distribution on the cathode surface; the side sealing liquid groove 41 of the cathode fixture 4 can effectively reduce the gathering of electric field lines at the edge of the mold core.
[0092] In the post-processing of the metal microstructure core, first remove the Si on the surface of the metal microstructure core, prepare a 30wt% NaOH solution, specifically weigh 30g of sodium hydroxide and put it in a beaker, measure 70mL of water with a measuring cylinder and pour it into the beaker, and stir evenly. Immerse the core in the NaOH solution, increase the water bath temperature of the ultrasonic cleaner to 80°C, use a beaker clamp to fix the beaker containing the core and the NaOH solution in the ultrasonic cleaner, and stir ultrasonically at a power of 100W for 20min. Repeat the operation several times, and after Si is removed, take out the core; immerse the core in an acetone solution to remove the SU-8 glue on the surface, and also use ultrasonic stirring to accelerate the solution of the SU-8 glue, and the ultrasonic treatment temperature is room temperature; finally, immerse the core in anhydrous ethanol and ultrasonically treat it at room temperature for 30min to complete the post-processing process of the core.
[0093] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0094] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A segmented electroforming method for a metal microstructure core, characterized in that: The metal microstructure mold core is divided into a microstructure layer, a transition layer and a base layer, wherein the thickness of the microstructure layer is 0.5 times the width of the characteristic microstructure in the metal microstructure mold core; the thickness of the transition layer is 220 µm, and the thickness of the base layer is the total thickness of the metal microstructure mold core minus the thickness of the microstructure layer and the transition layer; the segmented electroforming method comprises the following steps: S1. Photolithography and pre-processing of electroplating master mold; S2. Arrange the electroforming device and set the power supply parameters: install the electroforming mother mold on the cathode fixture containing the side sealing liquid tank, the side sealing liquid tank is used to suppress the edge effect of the casting layer cathode, the cathode fixture is installed on the rotating mechanism, an insulating shielding baffle with a through hole is arranged between the electroforming mother mold and the anode, two flushing ports are symmetrically arranged in the electroforming tank, the two flushing ports are aligned with the through hole of the insulating shielding baffle and the electroforming mother mold, and the electroforming liquid impacts the electroforming mother mold, and the electroforming liquid is mainly nickel sulfamate; according to the thickness of each electroforming layer, the power supply parameters of each electroforming layer are correspondingly set on the same pulse power supply; S3. Using a current density of 0.5-1A / dm on the electroforming master mold 2 The microstructure layer is formed by direct current or reverse pulse current electroforming: For the microstructure layer with an aspect ratio less than or equal to 1, a current density of 0.5-1A / dm 2 The electroforming master mold is rotated while applying a direct current to perform electroforming; For the microstructure layer with an aspect ratio greater than 1, a reverse pulse current is used while rotating the electroforming master mold for electroforming. One pulse cycle of the reverse pulse current includes a positive current and a negative current. The frequency of the reverse pulse current is 0.1-10 Hz, and the forward current density is 1 A / dm 2 , the positive-negative pulse ratio is 1:6, and the negative pulse duty cycle is 0.1-0.2; S4. Forming the transition layer on the microstructure layer by electroforming with a positive pulse current: switching the current of the electroformed microstructure layer to a positive pulse current without interruption, and forming the transition layer on the microstructure layer by electroforming with a positive pulse current, wherein the frequency of the positive pulse current is 800 Hz and the average current density is 1 A / dm 2 , the duty cycle is 0.5; S5. Using a current density of 3-5A / dm on the transition layer 2 The base layer is formed by electroforming with a direct current: the positive pulse current of the electroforming transition layer is switched continuously to a current density of 3-5A / dm 2 A direct current is applied to electroform the base layer on the transition layer; S6. Post-processing of the metal microstructure core after electroforming.
2. The segmented electroforming method of the metal microstructure mold core according to claim 1, characterized in that: The thickness of the transition layer is determined based on simulation and experimental results. The thermal stress generated by the temperature load is used to simulate the stress caused by the expansion or contraction of the transition layer. The relationship between the tensile stress and the temperature load measured in the experiment is established based on the following two formulas, and the relationship between the change in the thickness of the transition layer and the warpage deformation is analyzed. In the experiment, a transition layer of 60-260µm is electroformed on a single mirror-polished silicon substrate, and the maximum warpage deformation is tested using an ultra-depth of field microscope. When both the experimental and simulation results show that when the thickness of the transition layer is 220µm, the maximum warpage deformation no longer changes; ; ; In the formula represents the temperature load change, represents Poisson's ratio, represents the elastic modulus, represents the experimentally measured tensile stress, is the coefficient of thermal expansion, represents the process temperature, Indicates the equivalent reference temperature.
3. The segmented electroforming method of the metal microstructure core according to claim 1, characterized in that: In step S3, for the microstructure layer with an aspect ratio less than or equal to 1 and for the microstructure layer with an aspect ratio greater than 1, the rotation speed of the electroforming master mold is 120 r / min.
4. The segmented electroforming method of the metal microstructure mold core according to claim 1, characterized in that: In step S1, photolithography and pre-processing of the electroforming master mold includes the following steps: S11. Design a polymer micro-device mask, introduce an edge micro-groove structure, select a negative SU-8 photoresist as the lithography object, and complete the preparation of the electroplating master mold through the processes of coating, pre-baking, exposure, post-baking, development and hardening; S12. A layer of titanium or chromium is plated on the electroforming master mold as a bonding layer; S13. A layer of metal platinum is plated on the bonding layer as a conductive layer.
5. The segmented electroforming method of the metal microstructure core according to claim 4, characterized in that: In step S12, the vacuum degree is 5×10 -2 MPa and a sputtering current of 100-120 mA, and the sputtering time is 100-200 s; In step S13, the vacuum degree is 5×10 -2 The conductive layer is plated under the conditions of a pressure of 100 MPa and a sputtering current of 35 mA, and the sputtering time is 100-300 s.
6. The segmented electroforming method of the metal microstructure core according to claim 4, characterized in that: In step S6, post-processing the electroformed metal microstructure mold core includes the following steps: S61. Prepare a sodium hydroxide solution, place the metal microstructure core into the solution, and dissolve silicon by ultrasonic stirring and heating the sodium hydroxide solution; S62. The metal microstructure mold core is then placed in an acetone solution and the SU-8 photoresist on the surface is removed by ultrasonic stirring; S63. Finally, the metal microstructure mold core is placed in an ethanol solution, and the residual SU-8 photoresist in the microstructure layer is removed by ultrasonic treatment.
7. The segmented electroforming method of the metal microstructure core according to claim 6, characterized in that: In step S61, a 30 wt% sodium hydroxide solution is prepared, the heating temperature is 80° C., the ultrasonic power is 100 W, and the stirring time is 20 min; In step S62, the temperature of ultrasonic treatment is room temperature; In step S63, ultrasonic treatment is performed at room temperature for 30 minutes.